Techno‐economic analysis of metal hydride‐based energy storage system in microgrid. Issue 3 (27th May 2019) - Kumar, Kuldeep; Alam, Mohd; Dutta, Viresh
Abstract: Hydrogen can be a promising option as an energy storage medium in renewable power generator‐based microgrid. However, the technologies used for the hydrogen storage such as high pressure in gaseous form and solid storages can significantly affect the cost performance of the hydrogen‐based microgrid. In this study, a techno‐economic assessment for solid hydrogen storage (metal hydride [MH])‐based microgrid in Indian operating conditions has been carried out in terms of levelized cost of electricity (LCOE), net present cost, and avoided environmental emissions. In the present microgrid, excess photovoltaic (PV) generator electricity is used to generate hydrogen using the alkaline water electrolyzer (EL). This generated hydrogen is stored in the MH cylinder. The stored hydrogen is converted back into electricity by fuel cell (FC) in case of insufficiency of PV electricity. The sizing of the microgrid components such as PV, FC, EL, and hydrogen storage tank are obtained for given load profile using HOMER optimization tool. An attempt has been made for the cost evaluation of the solid and high‐pressure gaseous storages in the microgrid. A comparative study between two energy storage mediums such as battery and hydrogen in microgrid is also performed. In case of battery and hydrogen storages, the LCOE is found to be 0.1293 and 0.383 $/kWh, respectively. It was found that battery storage system is more economical than hydrogen storage in microgrid. Nonetheless, the difference between the LCOE in hydrogen‐based microgrid is reduced considerably with optimized cost scenario of the EL, FC, and H2 storage tank as compared to the battery storage. Such technical, economic, and environmental assessment of the MH‐based microgrid system provides a firm basis to policymakers for shaping energy and environment policies for hydrogen activities. Abstract :